Thoracoscopic excision of a large posterior mediastinal lipoblastoma in a 4 year old girl: Review of literature - Natasha L. Vageriya; Sachin S. Patil; Hussain Kotawala; Hemangi Athawale; Nitin P. Dhende; Shivaji B. Mane (Elsevier, 2016)
Majority of lipoblastomas arise in the superficial tissues of the extremities, but they can occasionally be found in neck and abdomen. Lipomatous tumors located in the mediastinum are extremely rare, and if found they are more commonly located in anterior mediastinum than in the posterior. We report a case of large posterior mediastinal lipoblastoma extending into the superior mediastinum in a 4 year old girl. Child presented with respiratory distress. The computed tomography scan was suggestive of posterior and superior mediastinal fat attenuating non-enhancing mass of size 6.5 × 4.8 × 2.7 cm complete thoracoscopic excision of mass was done. Histopathology of the excised specimen was suggestive of lipoblastoma. At 3 months follow-up. There is no residual tumor or recurrence.